2008
DOI: 10.2108/zsj.25.123
|View full text |Cite
|
Sign up to set email alerts
|

Social Environment and Sex Differentiation in the False Clown Anemonefish, Amphiprion ocellaris

Abstract: Plasticity in sex differentiation is known to be common in teleost fishes. Anemonefishes are protandrous; females are the largest and dominant members of social groups, displaying frequent aggressive behavior towards other members of groups. The second-ranked individuals become males and others remain as non-reproductive individuals. Here we examine the influence of social interaction in-group on sex differentiation in the false clown anemonefish, Amphiprion ocellaris, under laboratory conditions. Three juveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 24 publications
3
43
1
1
Order By: Relevance
“…The AVT neural phenotype occurs independently of gonadal influence (Semsar and Godwin 2003) and the A. ocellaris that we used were immature and not yet sexually differentiated. Although dominant individuals tended to have greater GSIs in the current study, our previous study demonstrated that sex differentiation was not induced within 180 days of social rank formation, during which time there were no significant differences in serum sex steroid levels or the proportion of testicular tissue in the gonads (Iwata et al 2008). Our preliminary study also revealed that there were no significant differences in the ratio of testicular or ovarian tissue, or in the development of these cells compared with GHC fish after 90 days of group formation.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…The AVT neural phenotype occurs independently of gonadal influence (Semsar and Godwin 2003) and the A. ocellaris that we used were immature and not yet sexually differentiated. Although dominant individuals tended to have greater GSIs in the current study, our previous study demonstrated that sex differentiation was not induced within 180 days of social rank formation, during which time there were no significant differences in serum sex steroid levels or the proportion of testicular tissue in the gonads (Iwata et al 2008). Our preliminary study also revealed that there were no significant differences in the ratio of testicular or ovarian tissue, or in the development of these cells compared with GHC fish after 90 days of group formation.…”
Section: Discussioncontrasting
confidence: 58%
“…AVT neurons innervate the corticotrophic cells of the pituitary in the green molly, Poecilia latipinna (Batten et al 1990), and they influence adrenocorticotropin and thus cortisol secretion in the rainbow trout, Oncorhynchus mykiss (Baker et al 1996). Plasma cortisol was not measured in the current study, and the stress level of each individual was not clear, but our previous study indicated growth and reproductive suppression in c individuals after 180 days of group housing (Iwata et al 2008). It is conceivable that AVT neurons might be involved in cortisol secretion that leads to growth or reproductive suppression in c fish.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…A PVC waterpipe joint (50 mm diameter) substituted for a host sea anem-one [6] and was placed at the center of the experimental tank as a shelter. Each individual in a tank was identified by differences in the white-striped pattern on its body and classified as (dominant) or (second-ranked) from behavioral observations on Day 0 of the experiment [6].…”
Section: Animalsmentioning
confidence: 99%